POTENSI LUMBROKINASE DENGAN CARRIER N,N,N-TRIMETIL KITOSAN KLORIDA (TMC) MENGGUNAKAN LIGAND C-RGD SEBAGAI AGEN FIBRINOLITIK DAN ANTI-PLATELET TERBARUKAN - Firsty, Naufal Nandita; Furqan, Muhammad; Aritonang, Ilman Arif (Essence of Scientific Medical Journal; Vol 19 No 1 (2021): Volume 19 No. 1 (Januari - Juni 2021) Essential: Essence of Scientific Medical Journal, 2021)
Introduction: Venous thrombosis is the third most cardiovascular disease in the world. Administration of fibrinolytic agents such as streptokinase is the chosen treatment of the disease. However, the disadvantages are short half-time, unspecific to fibrin, poor targeting, expensive price, and tend to cause bleeding. Therefore another fibrinolytic agent is needed to cope with some of the deficiencies and side effects of current fibrinolytic agents. This literature review aims to explain the potential of lumbrokinase with TMC carrier and c-RGDligand as a renewable fibrinolytic and antiplatelet agent. The method used in this literature review is a literature study using the last 10 years of journal gained from some search engines such as ScienceDirect, PubMed, Google Scholar, and ClinicalKey. Discussion: Lumbrokinase is an enzyme from the extraction of the earthworm’s digestive tract which consists of several serine protease isoenzymes. As a fibrinolytic agent, lumbrokinase can hydrolyze both fibrin or fibrinogen and also activate plasminogen into plasmin. Besides, lumbrokinase is known as has an antiplatelet effect as aspirin has. The use of TMC as the carrier can increase the bioavailability of lumbrokinase. Meanwhile, the addition of c-RGD ligand can increase the specificity preventing fibrinogen to bind the GPIIb/IIIa receptor thereby inhibiting thrombus formation. Conclusion: From various in vitro and in vivo studies, it was concluded lumbrokinase with carrier TMC and c-RGD ligand can accelerate thrombolysis, and reduce the risk of bleeding so that it’s potentially a renewable fibrinolytic and antiplatelet agent. However, further research is needed regarding therapeutic doses, side effects, and toxicity studies.